PERKUATAN BALOK BETON BERTULANG AKIBAT TEGANGAN TARIK MENGGUNAKAN SERAT SABUT KELAPA - Diana Permatasari; Yusuf Amran; Chica Oktavia (Prodi Teknik Sipil Universitas Muhammadiyah Metro, 2026)
This study aims to examine the effect of horizontally arranged coconut coir fibers with varying spacing on the flexural tensile strength of concrete. The research was conducted experimentally in a laboratory using a planned concrete strength of fs 45 MPa. The test specimens were concrete beams measuring 15 × 15 × 60 cm with a total of 9 specimens, consisting of normal concrete, concrete with coconut coir fibers spaced at 2.5 cm, and concrete with coconut coir fibers spaced at 5 cm. Flexural tensile strength testing was carried out at the age of 28 days using the two-point loading method in accordance with SNI 4431:2011.The results indicate that the addition of horizontally arranged coconut coir fibers significantly increases the flexural tensile strength of concrete. Concrete with a fiber spacing of 2.5 cm showed an increase in flexural tensile strength of 47.6% compared to normal concrete, while concrete with a fiber spacing of 5 cm exhibited an increase of 13.9%. Closer fiber spacing provides a more optimal improvement in flexural tensile strength due to the ability of the fibers to restrain and distribute tensile stresses within the concrete. This study demonstrates that coconut coir fiber has strong potential as an environmentally friendly and sustainable concrete admixture